(untitled) (Nóema, 2013)
This note deals with Francesco Emmolo’s essay and aims to consider EnzoPaci’s philosophical proposal in the light of a question about the “knowing subject”. The history of philosophy has presented many images of it, which engage in a critical confrontation with the common understanding of the knowledgerelation.